Cardiogenic shock due to reverse takotsubo syndrome triggered by multiple sclerosis brainstem lesions: a case report and mini review - Brandner, Joas; Lu, Henri; Muller, Olivier; Eskioglou, Elissavet; Chiche, Jean-Daniel; Antiochos, Panagiotis; Chocron, Yaniv (Frontiers in Cardiovascular Medicine, 2023)
Background Takotsubo syndrome (TTS) is mainly characterized by chest pain, left ventricular dysfunction, ST-segment deviation on electrocardiogram (ECG) and elevated troponins in the absence of obstructive coronary artery disease. Diagnostic features include left ventricular systolic dysfunction shown on transthoracic echocardiography (TTE) with wall motion abnormalities, generally with the typical “apical ballooning” pattern. In very rare cases, it involves a reverse form which is characterized by basal and mid-ventricular severe hypokinesia or akinesia, and sparing of the apex. TTS is known to be triggered by emotional or physical stressors. Recently, multiple sclerosis (MS) has been described as a potential trigger of TTS, especially when lesions are located in the brainstem. Case summary We herein report the case of a 26-year-old woman who developed cardiogenic shock due to reverse TTS in the setting of MS. After being admitted for suspected MS, the patient presented with rapidly deteriorating clinical condition, with acute pulmonary oedema and hemodynamic collapse, requiring mechanical ventilation and aminergic support. TTE found a severely reduced left ventricular ejection fraction (LVEF) of 20%, consistent with reverse TTS (basal and mid ventricular akinesia, apical hyperkinesia). Cardiac magnetic resonance imaging (MRI) performed 4 days later showed myocardial oedema in the mid and basal segments on T2-weighted imaging, with partial recovery of LVEF (46%), confirmed the diagnosis of TTS. In the meantime, the suspicion of MS was also confirmed, based on cerebral MRI and cerebral spinal fluid analyses, with a final diagnosis of reverse TTS induced by MS. High-dose intravenous corticotherapy was initiated. Subsequent evolution was marked by rapid clinical improvement, as well as normalization of LVEF and segmental wall-motion abnormalities. Conclusion Our case is an example of the brain-heart relationship: it shows how neurologic inflammatory diseases can trigger a cardiogenic shock due to TTS, with potentially serious outcomes. It sheds light on the reverse form, which, although rare, has already been described in the setting of acute neurologic disorders. Only a handful of case reports have highlighted MS as a trigger of reverse TTS. Finally, through an updated systematic review, we highlight the unique features of patients with reversed TTS triggered by MS.